Particle swarm optimisation applications in FACTS optimisation problem - Jordehi, Ahmad Rezaee; Jasni, Jasronita; Abdul Wahab, Noor Izzri; Ab Kadir, Mohd Zainal Abidin (IEEE, 2013)
FACTS optimisation is one of the most important and difficult problems in power systems. For solving this problem, so many different approaches have been proposed in the literature. Among them, particle swarm optimisation (PSO) has exposed so promising behavior. In this paper, applications of PSO in FACTS optimisation problem are explained and analysed from the viewpoint of the objectives, used basic PSO variant, PSO parameter selection, multi-objective handling, constraint handling and discrete variable handling. Eventually, some hints for future research is provided.